Rendimento da carne mecanicamente separada in natura e pós defumação obtida do bagre africano abatido em diferentes classes de peso - Daga, Joaquim Antônio (2016)
The objective of this experiment was to evaluate the Yield of the mechanically deboned meat (CMS) in natura and after smoking obtained of the african catfish (Clarias gariepinus) slaughtered in different weight classes (class 1: 0,214 to 0,402 kg; class 2: 0,538 to 0,634 kg; class 3: 0,780 to 1,000 kg; class 4: 1,132 to 1,314 kg and class 5: 1,396 to 1,706 kg), the end of the smoking process was performed acceptance testing with the participation of 38 judges. We used 93 fish distributed in a completely randomly design composed by five treatments and 16 repetitions. We evaluated the percentage yields of: truncated clean (RTL), residues of the clean trunk (Res. TL), CMS in natura (RCMS), residues of the CMS (Res. CMS), and smoked CMS (RCMSD); and the chemical-physical composition of the CMS in natura and smoked CMS. The data were subjected the analysis of variance and, when observed statistical difference, the Tukey test was applied by 5 % of probability. The yield of clean trunk was higher and did not differ among the weight classes 2, 3, 4 and 5. The yield of the CMS regarding the clean truncated weight did not differ among the treatments. There was no significant difference (P>0.05) of the yields among the weight classes during the smoking process. The values of the chemical-physical analysis for CMS in natura were near to the considered ones in the literature for the same species, being considered, according to the lipids levels, a semi-fat meat of fish. The chemical-physical composition of smoked CMS had an increase in the protein levels, lipids and ashes compared to CMS in natura, however the moisture values were lower when compared with the CMS in natura, resulted from the dehydration occurred during the smoking process. The yields of the smoked CMS did not differ among the treatments. For the results of the acceptance test, we observed no significant difference among the weight classes, obtaining average values near to seven, which corresponds to “I liked lightly”. Based on the obtained information, we can conclude that the african catfish can be slaughtered and processed from 0,600kg by presenting higher yield of clean trunk, lower waste quantity, satisfactory organoleptic characteristics and higher consumption frequency.